Proceedings of the 2018 Workshop on Privacy in the Electronic Society 2018
DOI: 10.1145/3267323.3268958
|View full text |Cite
|
Sign up to set email alerts
|

What's a Little Leakage Between Friends?

Abstract: This paper introduces a new attack on recent messaging systems that protect communication metadata. The main observation is that if an adversary manages to compromise a user's friend, it can use this compromised friend to learn information about the user's other ongoing conversations. Specifically, the adversary learns whether a user is sending other messages or not, which opens the door to existing intersection and disclosure attacks. To formalize this compromised friend attack, we present an abstract scenari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…We focus on the global adversary threat model as that is the real-world adversary to combat today in the context of MPCS. We include systems that are secure even when a client's correspondent is adversarial and those that are not [6].…”
Section: Metadata-protecting Communication Systems (Mpcs)mentioning
confidence: 99%
See 2 more Smart Citations
“…We focus on the global adversary threat model as that is the real-world adversary to combat today in the context of MPCS. We include systems that are secure even when a client's correspondent is adversarial and those that are not [6].…”
Section: Metadata-protecting Communication Systems (Mpcs)mentioning
confidence: 99%
“…Atom uses the square network by Hรฅstad [34], which can permute ๐‘š elements using โˆš ๐‘š nodes with each shuffling โˆš ๐‘š ciphertexts and connects to โˆš ๐‘š nodes in the subsequent layer. 6 In Atom each logical server in this network is realized by a group of physical servers such that the anytrust assumption holds over the group. The number of servers in each group is tuned to ensure that given the total number of servers, and knowledge that up to a bounded fraction of them can be malicious, at least one server in each group should be honest with very high probability.…”
Section: Mixnet Based Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior works on MPMs have shown that the proposed contact discovery, add-friend, dialing, and conversation protocols are secure and leak little information (negligible or bounded) on their own, but surprisingly, none had carefully looked at their composition. Indeed, recent work by Angel et al [9] shows that existing dialing and communication protocols do not actually compose in the presence of compromised friends. The reason is that the number of communication channels (k) is usually smaller than the number of friends that could dial the user at any one time.…”
Section: A Channel Allocation Can Leak Informationmentioning
confidence: 99%
“…This is significant because MPMs are designed precisely to avoid side-channel attacks. In particular, Angel et al [9] show that these systems are secure only if none of the contacts with whom a user communicates are compromised by an adversary; otherwise, compromised contacts can learn information about the user's other conversations. We expand on Angel et al's observation in Section II, and show that it is an instance of an allocation-based side-channel attack.…”
Section: Introductionmentioning
confidence: 99%